2022
DOI: 10.1155/2022/6405400
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary Study on the Therapeutic Effect of Doxorubicin-Loaded Targeting Nanoparticles on Glioma

Abstract: Doxorubicin (DOX) is an anthracycline anticancer drug, which is often associated with drug resistance and cytotoxicity. More unfortunately, the biological barrier in the human environment can weaken the efficacy of DOX, such as the blood-brain barrier (BBB). This work attempts to make efforts to solve this problem. We used polyethylene glycol distearoylphosphatidylethanolamine (PEG-DSPE) as a nanocarrier and DOX as a model drug to construct a composite nanodrug (TF-PEG-DSPE/DOX NPs) by coupling transferrin (TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Additionally, mechano-signaling elements function in close association with the intercellular junction proteins, which can influence the penetration of drugs across cell layers. To probe the impact of CMV-induced changes on the efficiency of drug delivery within glioma spheroids we used doxorubicin, a commonly used antitumor drug against high grade gliomas. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, mechano-signaling elements function in close association with the intercellular junction proteins, which can influence the penetration of drugs across cell layers. To probe the impact of CMV-induced changes on the efficiency of drug delivery within glioma spheroids we used doxorubicin, a commonly used antitumor drug against high grade gliomas. , …”
Section: Introductionmentioning
confidence: 99%
“…To probe the impact of CMV-induced changes on the efficiency of drug delivery within glioma spheroids we used doxorubicin, a commonly used antitumor drug against high grade gliomas. 30,31…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%